Gentelligence: The Revolutionary Approach to Leading an Intergenerational Workforce - Gerhardt, Megan; Nachemson-Ekwall, Josephine; Fogel, Brandon (Rowman & Littlefield Publishers, 2021)
"Vital for any organization with multigenerational staffs, and for marketers, public relations professionals, HRD managers, or executives." Library Journal, Starred Review Gentelligence: The Revolutionary Approach to Leading an Intergenerational Workforce presents a transformative way to end the generational wars once and for all. This book first introduces Gentelligence as a powerful business strategy and shows why it is critical for the future of work. It then presents a practical guide and a call to action for leaders of all ages to unlock the potential strengths of each generation. Readers will learn how an intergenerational workforce can be reframed as a profound business opportunity and discover how Gentelligence can help them win the talent war, create strong, diverse teams, and build adaptable cultures that will flourish in an era of rapid change. Gentelligence shares groundbreaking evidence that will have readers thinking about their generationally diverse workforce in an entirely different way. Readers will discover: Where generational conflict originates, and how it results in both dangerous ageism and reverse ageism in today’s workplaces. Why the generation gap stems from a misunderstanding of shared core values across all generations. How to find essential common ground with colleagues, both older and younger, and recognize the unique needs that come with different generational identities. How generational shaming leads us to view those from other generations as competitors rather than collaborators, further damaging employee engagement, team dynamics, innovation, and organizational culture. How leveraging the unique strengths of each generation at work can lead to a win-win outcome for all. How traditional views on leadership have been turned upside down as a result of new generational dynamics, with many employees currently being led by managers that are younger than themselves, and older leaders struggling to make sense of changing norms around authority and power. Gentelligence reveals the opportunities within an intergenerational workforce and provides actionable tools to help leaders build Gentelligent organizations. Unlike other books on generational leadership, this book rejects common stereotypes assigned to different generations, replacing them with a deep understanding of why those who grew up in different times may behave in unique and valuable, ways. We challenge leaders to go beyond simply accepting generational differences to leverage them proactively to increase engagement, innovation, and organizational success.